2017
DOI: 10.1002/jso.24956
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous hepatic perfusion with melphalan in uveal melanoma: A safe and effective treatment modality in an orphan disease

Abstract: BackgroundMetastatic uveal melanoma (UM) carries a poor prognosis; liver is the most frequent and often solitary site of recurrence. Available systemic treatments have not improved outcomes. Melphalan percutaneous hepatic perfusion (M‐PHP) allows selective intrahepatic delivery of high dose cytotoxic chemotherapy.MethodsRetrospective analysis of outcomes data of UM patients receiving M‐PHP at two institutions was performed. Tumor response and toxicity were evaluated using RECIST 1.1 and Common Terminology Crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
89
0
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 24 publications
14
89
0
15
Order By: Relevance
“…An initial randomized Phase III study completed several years ago and showed an improvement in hepatic PFS (7.0 vs 1.6 months; p < 0.0001) when compared with investigators' choice, however no improvement in overall survival was observed (10.6 vs 10.0 months; p = 0.77), although this may have been partly due to patient crossover [16]. More recently, a case series combining data from two major centers reported a median overall survival of 15 months in 51 patients [17]. These results, while encouraging, require confirmation in a randomized study and an international Phase III (FOCUS, NCT026786572) comparing percutaneous hepatic perfusion with investigator choice is currently enrolling patients.…”
mentioning
confidence: 94%
“…An initial randomized Phase III study completed several years ago and showed an improvement in hepatic PFS (7.0 vs 1.6 months; p < 0.0001) when compared with investigators' choice, however no improvement in overall survival was observed (10.6 vs 10.0 months; p = 0.77), although this may have been partly due to patient crossover [16]. More recently, a case series combining data from two major centers reported a median overall survival of 15 months in 51 patients [17]. These results, while encouraging, require confirmation in a randomized study and an international Phase III (FOCUS, NCT026786572) comparing percutaneous hepatic perfusion with investigator choice is currently enrolling patients.…”
mentioning
confidence: 94%
“…Although survival results are still pending, it is of clinical relevance to share the results on safety and toxicity in advance. The aim of this paper was to report all safety and toxicity results and compare these with historical data from studies on M-PHP using the first-generation filter [ 1 , 6 , 8 , 11 , 12 ]. Our data on the efficacy of M-PHP with the GEN 2 filter will be reported separately.…”
Section: Introductionmentioning
confidence: 99%
“…This may raise concern for an increased risk of myelosuppression in the latter technique. However, "most" patients treated with isolated limb perfusion received granulocyte colony-stimulating factor [9]. On the contrary, our single patient did not have evidence of myelosuppression.…”
Section: Discussionmentioning
confidence: 45%
“…The drug choice of melphalan is grounded in clinical responses noted in the treatment of cutaneous melanoma by isolated limb perfusion and liver metastases of uveal melanoma by isolated hepatic perfusion [5,6,9]. Preclinical data support the therapeutic response of human melanoma lines to melphalan and have shown an enhanced response with hyperthermia [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation